2012
DOI: 10.5430/jnep.v3n3p44
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative oral health education for caregivers in an assisted-living facility

Abstract: Background: The purpose of this study was to implement a collaborative oral health project and evaluate its effectiveness for caregivers in an assisted-living facility. An interdisciplinary study was conducted by nursing and dental hygiene faculty. Methods:A quasi-experimental design was utilized with a pre-post treatment format. Pre-and post-treatment scores were analyzed from a convenience sample of 13 caregivers in an assisted-living facility. The information addressed oral care assessments, interventions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…A follow-up self-reported survey conducted 7.5 months later also showed that staff continued to use the education resources and oral hygiene products provided by Parsons. [21] However, not all oral health education programs are successful in changing nursing staff's perceptions, knowledge, and behaviors of oral health care provided to patients. Gammack and Pulisetty [16] examined the effectiveness of an oral health education program but unfortunately the 30-minute multimedia education program found no statistical significance in the nurses' quality of oral health care before and after the intervention.…”
Section: Oral Health and Nursing Staffmentioning
confidence: 99%
“…A follow-up self-reported survey conducted 7.5 months later also showed that staff continued to use the education resources and oral hygiene products provided by Parsons. [21] However, not all oral health education programs are successful in changing nursing staff's perceptions, knowledge, and behaviors of oral health care provided to patients. Gammack and Pulisetty [16] examined the effectiveness of an oral health education program but unfortunately the 30-minute multimedia education program found no statistical significance in the nurses' quality of oral health care before and after the intervention.…”
Section: Oral Health and Nursing Staffmentioning
confidence: 99%